Kecerdasan Intelektual Terhadap Keharmonisan Rumah Tangga di Kelurahan Tegal Sari III Kecamatan Medan Area - Harahap, Nurul Aini; Adenan, Adenan; Siregar, Husna Sari (Medan Resource Center, 2023)
Intellectual intelligence is one of the main factors in society in building household harmony. The community in Tegal Sari III Subdistrict, Medan Area District, shows that the intellectual intelligence factors for household harmony are inseparable from the existence of faith in each partner so that the better the relationship with Allah SWT, the calmer and more confident in dealing with existing problems, understanding each other. partners, helping each other in economic matters, making commitments made with partners, for example, loyalty, honesty, and openness, and sincerity to accept the weaknesses and strengths of their partners. After conducting research, this research focuses on Intellectual Intelligence on Household Harmony in Tegal Sari III Village, Medan Area District. Intellectual intelligence becomes quite an interesting conversation, especially with regard to household harmony. A harmonious household is everyone's dream, but creating a harmonious household is not an easy thing, because it requires intellectual intelligence. Intellectual abilities are also based on a person's capability to act purposefully, think meaningfully, and be able to interact efficiently with their environment. So that intellectual intelligence becomes one of the important roles for household harmony. The method used in this study is the method of observation, documentation and interviews. Research data were analyzed using descriptive analysis method. which includes: data collection, data filtering, data classification drawing conclusions.